EXPLORING UNDERGRADUATE PUBLIC SPEAKING ANXIETY: A NARRATIVE INQUIRY WITH EFL STUDENT IN INDONESIAN UNIVERSITY - wati, ayu Ambar (Critical Review of English-Arabic World Journal is an open-access journal published by the Language Development Unit, State Islamic University of Kiai Haji Achmad Siddiq, Jember, 2024)
ABSTRACT/مستخلص البحث What have to do for undergraduate student in EFL student to identify public speaking anxiety based on student experience. This research exploring undergraduate student public speaking anxiety experience . To know about public speaking anxiety undergraduate with EFL student. Can be identifying public speaking anxiety when on the performance This study was drawn upon contructivism paradigms. We employed the qualitative narrative inquiry Barkhuizen et al., 2014 Clandinin & Connelly, 1996 Connelly & Clandinin, 1990) to extract their experiences in such settings. We considered this inquiry as the most appropriate research design as it can exploring the undergraduate student public speaking anxiety with EFL student in Indonesian University. Two people in all voluntarily participated in this study. When it came to choosing participants, we used the ethical selection techniques suggested by Hammersley and Traianou (2012). First and foremost, researchers must honor the abilities and viewpoints of each participant in this study. The participants in the study have the right to revoke their consent at any moment, and the researcher must receive a letter of consent from them in order for them to enroll in the study. This study was designed to explore the experiences of undergraduate students for public speaking anxiety during speaking in the classroom. Including students performance, interaction student with audience. The interview was part of a study by Hook, Valentiner, and Connelly (2013) that looked into the causes and effects of performance anxiety and interaction anxiety among students in a classroom. When asked if their students'' fear was related to speaking in front of others or to learning a second language, participant said that her pupils'' worry was